T-Scan II computerized occlusal analysis - Lazić Vojkan; Živković Slavoljub; Popović Gorjana (Serbian Medical Society - Dental Section, Belgrade, 2004)
Occlusal analysis using computerized technology has become a part of modern information technology. The aim of this study was to show the possibilities of T-Scan II computerized occlusal analyzer in prosthetic and restorative postinsertion occlusal problems. The T-Scan II computerized occlusal analysis (Tekscan, Boston, USA) is an integral part of clinical functional analyses in prosthetic and restorative insertions. The T-Scan II computerized system can quickly determine prematurities, high points, regions of excessive force and nonuniform force concentration. It can also calculate disocclusion time accurately. Occlusal foil indicators can determine only the position, number and relative force of occlusal contacts.